The Role of Labor Law on Business Sustainability and Workers' Welfare in Indonesia - Siti Mufidatul Azizah; Chofifah Indah Parawansyah; Fitrotul Bita Aulia Putri; Reviby Adam Nazalla Dhias; Arif Zunaidi (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
This research discusses the Role of Labor Law on Business Sustainability and Workers' Welfare in Indonesia. In the context of economic growth and technological development, labor law serves as a tool to maintain a balance between business sustainability and the protection of workers' rights. This research uses a literature study method with a content analysis approach to examine various labor regulations such as Law No. 13 of 2003, the Job Creation Law, and the Workers' Welfare Law. Year 2003, the Job Creation Law, and the BPJS Law. The results show that compliance with labor law has a positive impact on operational stability, employee loyalty, and company competitiveness. However, implementation challenges such as lack of supervision, unlawful employment contracts, and low legal literacy of workers are still an obstacle. Therefore, synergy between the government, companies, and workers is needed to create a healthy and productive work environment.